The Influence of Corporate Culture, Competency, and Training & Development on Employee Performance with Leadership as an Intervening Variable - Nurul Rohmah; Nurul Qomariyah; Ni Nyoman Putu Martini; Eko Budi Satoto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The competitive nature of the skincare and healthy care industry demands companies to have a strong corporate culture, competent employees, and effective leadership to achieve optimal performance. This study aims to examine the influence of corporate culture, competence, training & development on employee performance with leadership as a mediating variable at PT. FTWO Sukses Globalindo Banyuwangi. The study population consisted of 117 employees with a sample of 102 respondents. The analysis method used was Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that corporate culture, competence, and training & development have a positive and significant effect on employee performance. Leadership was proven to act as a mediating variable that strengthens the influence of these three variables on performance. These findings indicate that the stronger the corporate culture, the higher the employee competence, and the more effective the training and development programs carried out, the more optimal employee performance will be through effective leadership. This study recommends that companies continue to strengthen the implementation of an adaptive corporate culture, improve competency development programs based on job needs, and encourage participatory and transformational leadership styles to maintain the sustainability of employee performance improvements in the long term.